2010
DOI: 10.1177/0022034509357309
|View full text |Cite
|
Sign up to set email alerts
|

Apatite Containing Aspartic Acid for Selective Protein Loading

Abstract: Physico-chemical modifications of hydroxyapatite (HAp) materials are considered as pre-requisites for the development of new bioactive carrier materials for drug delivery and tissue engineering applications. Since acidic amino acids have well-documented affinities to both HAp and basic proteins, HAp modified by aspartic acid (Asp, acidic amino acid) might be one of the candidate substrates for a basic protein carrier. Here, we synthesized HAp in the presence of various concentrations of Asp and observed that H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
(20 reference statements)
1
13
2
1
Order By: Relevance
“…The presence of Asp and Ser during HA preparation substantially reduced the crystallinity of HA (figure 2). Our results are in good agreement with the data reported by Uddin et al [19] in which the surface area increased twofold when 0.2 M Asp was added during HA preparation and the size of particles had an inverse relationship with their specific surface area. In a separate study, Gonzalez-McQuire et al [20] showed that the presence of amino acids inhibited the crystal growth of HA.…”
Section: Physico-chemical Properties Of Amino Acidfunctionalized Hydrsupporting
confidence: 93%
See 3 more Smart Citations
“…The presence of Asp and Ser during HA preparation substantially reduced the crystallinity of HA (figure 2). Our results are in good agreement with the data reported by Uddin et al [19] in which the surface area increased twofold when 0.2 M Asp was added during HA preparation and the size of particles had an inverse relationship with their specific surface area. In a separate study, Gonzalez-McQuire et al [20] showed that the presence of amino acids inhibited the crystal growth of HA.…”
Section: Physico-chemical Properties Of Amino Acidfunctionalized Hydrsupporting
confidence: 93%
“…For example, the calculated 1/n for the lysozyme adsorption onto Asp-HA is 0.848 (table 2), which shows a relatively high degree of homogeneity. For the BSA adsorption on Asp-HA, the Q m value was 16.23 mg g -1 (table 1), which is higher than that reported by Uddin et al [19] ). The extent of the first adsorbed protein layer (both BSA and lysozyme) onto HA depends on the strength of proteins -surface electrostatic interactions.…”
Section: Protein Adsorption On Amino Acid-functionalized Hydroxyapatitecontrasting
confidence: 55%
See 2 more Smart Citations
“…In fact, the interaction of HA with biological macromolecules, such as amino acids, is a promising method to control the surface charge of HA and thus influence the morphology of synthesized HA powder [23][24][25][26]. However, major aspects of the formation mechanism of enamel-like HA crystal synthesized on enamel are still unclear, e.g., HA nucleation, crystal growth and crystal orientation.…”
Section: Introductionmentioning
confidence: 99%